Design and fabrication of bicycle roller trainer indoor cycling / Abdul Hakim Abdullah - Abdullah, Abdul Hakim (2022)
This project aims to discover and learn the development of a bicycle roller using the SolidWorks 2019 to CAD modelling the project. This will be the learning process to study about the details of structure analysis of the bicycle roller main component by using SolidWorks 2019 simulation. Our proposed in this project is to develop CAD modelling the design of bicycle roller trainer, study on structure analysis of bicycle roller trainer main body frame using SolidWorks simulation. We will use SolidWorks for product design. This product design will be use as a basic guideline for new product manufacturer. This project also can help cyclist society in training requirement. In this project will includes the flowchart of the project, brainstorming ideas and planning schedule to complete the project flows. This project is expected to have a positive impact and can be achieved through the stated objectives.